Diluted Aqueous Dispersed Systems of 4-Aminopyridine: The Relationship of Self-Organization, Physicochemical Properties, and Influence on the Electrical Characteristics of Neurons - Ryzhkina, Irina; Murtazina, Lyaisan; Gainutdinov, Khalil; Konovalov, Alexander (Frontiers in Chemistry, 2021)
A variety of physicochemical methods were used to examine the self-organization, physicochemical, UV absorption, and fluorescent properties of diluted aqueous solutions (calculated concentrations from 1·10−20 to 1·10−2 M) of the membrane voltage-dependent potassium channels blocker 4-aminopyridine (4-AP). Using the dynamic light scattering method, it was shown that 4-AP solutions at concentrations in the range of 1·10−20–1·10−6 M are dispersed systems in which domains and nanoassociates of hundreds of nm in size are formed upon dilution. An interrelation between the non-monotonic concentration dependencies of the size of the dispersed phase, the fluorescence intensity (λex 225 nm, λem 340 nm), specific electrical conductivity, and pH has been established. This allows us to predict the bioeffects of the 4-AP systems at low concentrations. The impact of these diluted aqueous systems on the electrical characteristics of identified neurons of Helix lucorum snails was studied. Incubation of neurons in the 4-AP systems for which the formation of domains and nanoassociates had been established lead to a nonmonotonic decrease of the resting potential by 7–13%. An analysis of the obtained results and published data allows for a conclusion that a consistent change in the nature and parameters of the dispersed phase, as well as the pH of the medium, apparently determines the nonmonotonic nature of the effect of the 4-AP systems in a 1·10−20–1·10−6 M concentration range on the resting membrane potential of neurons. It was found that the pre-incubation of neurons in the 4-AP system with a concentration of 1·10−12 M led to a 17.0% synergistic decrease in the membrane potential after a subsequent treatment with 1·10−2 M 4-AP solution. This finding demonstrates a significant modifying effect of self-organized dispersed systems of 4-AP in low concentrations on the neurons’ sensitivity to 4-AP.